A fair playing field for sport. Issue 7 (8th June 2015) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings – For numerous people around the world, sport is a major part of their lives. Its popularity is evident in the degree of both active and passive involvement that prevails. Considerable scope therefore exists for sport to help a variety of interested parties to obtain income, additional value and influence. These include such as individual participants, organizations, sporting bodies, industries and governments. Such opportunities have risen further in recent decades as a result of gradual increases in professionalism and commercialism. But enjoying a high profile comes at a price. Conventional firms can vouch for that. In the wake of well-documented scandals that seriously damaged trust in business, the public quite rightly demanded that companies should demonstrate greater transparency and integrity. Sport has obviously not been without its problems either. Practical implications – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.